Modeling the Formation, Degradation, and Spatiotemporal Distribution of 2-Nitrofluoranthene and 2-Nitropyrene in the Global Atmosphere - Wilson, Jake; Octaviani, Mega; Bandowe, Benjamin A Musa; Wietzoreck, Marco; Zetzsch, Cornelius; Pöschl, Ulrich; Berkemeier, Thomas; Lammel, Gerhard (Environmental science & technology, 2020)
Polycyclic aromatic hydrocarbons (PAHs) are common atmospheric pollutants and known to cause adverse health effects. Nitrated PAHs (NPAHs) are formed in combustion activities and by nitration of PAHs in the atmosphere and may be equally or more toxic, but their spatial and temporal distribution in the atmosphere is not well characterized. Using the global EMAC model with atmospheric chemistry and surface compartments coupled, we investigate the formation, abundance, and fate of two secondarily formed NPAHs, 2-nitrofluoranthene (2-NFLT) and 2-nitropyrene (2-NPYR). The default reactivity scenario, the model with the simplest interpretation of parameters from the literature, tends to overestimate both absolute concentrations and NPAH/PAH ratios at observational sites. Sensitivity scenarios indicate that NO2-dependent NPAH formation leads to better agreement between measured and predicted NPAH concentrations and that photodegradation is the most important loss process of 2-NFLT and 2-NPYR. The highest concentrations of 2-NFLT and 2-NPYR are found in regions with strong PAH emissions, but because of continued secondary formation from the PAH precursors, these two NPAHs are predicted to be spread across the globe.
Keywords: polycyklické aromatické uhlovodíky; pyreny; Environmental Monitoring; látky znečišťující vzduch; monitorování životního prostředí; Pyrenes; fluoreny; atmosféra; Polycyclic Aromatic Hydrocarbons; Atmosphere; Air Pollutants; Fluorenes